THE INFLUENCE OF TEACHERS’ INTERACTIONAL TEACHING STYLE ON THE MOTIVATION TO LEARN INDONESIAN LANGUAGE FOR GRADE V STUDENTS IN ELEMENTARY SCHOOL - Ahmad Musahhal; Safrul (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study investigates the influence of teachers' interactional teaching style on fifth-grade students' motivation to learn the Indonesian language at Elementary School. Preliminary observation indicated that classroom participation remained low, with an average active involvement of only 35.4 percent across three sessions, a condition suspected to relate to teaching practices that had not fully optimized two-way dialogue and personal feedback. A quantitative correlational approach was employed through an explanatory survey with a cross-sectional design. The population consisted of 96 fifth-grade students, from which 61 students were drawn as the sample through cluster random sampling covering two class groups. Data were collected using two Likert-scale questionnaires that had passed validity and reliability testing, then analyzed through descriptive statistics, classical assumption tests, and simple linear regression. The results show that the regression equation is expressed as Ŷ = 15.966 + 0.482X, with a correlation coefficient of 0.520 and a coefficient of determination of 0.270. The t-test produced a calculated value of 4.675 against a table value of 2.001 at a significance level of 0.000018, indicating that the null hypothesis is rejected. These findings confirm that interactional teaching style contributes a positive and significant influence of 27.0 percent to students' learning motivation, while the remaining 73.0 percent is explained by factors outside the model. The study concludes that strengthening dialogic interaction and personal feedback in classroom practice is a strategic pathway for improving elementary students' motivation to learn Indonesian language.